Beyond High Courts : The Justice Complex in Latin America - Kapiszewski, Diana; Ingram, Matthew (Book collections on Project MUSE., 2018)
"Beyond High Courts: The Justice Complex in Latin America is a much-needed volume that will make a significant contribution to the growing fields of comparative law and politics and Latin American legal institutions. The book moves these research agendas beyond the study of high courts by offering theoretically and conceptually rich empirical analyses of a set of critical supranational, national, and subnational justice sector institutions that are generally neglected in the literature. The chapters examine the region's large federal systems (Argentina, Brazil, and Mexico), courts in Chile and Venezuela, and the main supranational tribunal in the region, the Inter-American Court of Human Rights. Aimed at students of comparative legal institutions while simultaneously offering lessons for practitioners charged with designing such institutions, the volume advances our understanding of the design of justice institutions, how their form and function change over time, what causes those changes, and what consequences they have. The volume also pays close attention to how justice institutions function as a system, exploring institutional interactions across branches and among levels of government (subnational, national, supranational) and analyzing how they help to shape, and are shaped by, politics and law. Incorporating the institutions examined in the volume into the literature on comparative legal institutions deepens our understanding of justice systems and how their component institutions can both bolster and compromise democracy and the rule of law. Contributors: Matthew C. Ingram, Diana Kapiszewski, Azul A. Aguiar-Aguilar, Ernani Carvalho, Natalia Leitão, Catalina Smulovitz, John Seth Alexander, Robert Nyenhuis, Sídia Maria Porto Lima, Jose Mario Wanderley Gomes Neto, Danilo Pacheco Fernandes, Louis Dantas de Andrade, Mary L. Volcansek, and Martin Shapiro"--